Hydrology principles and processes - Robinson, M.; Ward, R. C. (IWA Publishing, 2017)
The book comprises nine chapters, with seven core chapters dealing in detail with the basic principles and processes of the main hydrological components of the water cycle: precipitation, interception, evaporation, soil water, groundwater, streamflow and water quality. It takes a broadly non-mathematical approach, although some numeracy is assumed particularly in the treatment of evaporation and soil water. The introductory and concluding chapters show the relations and interactions between these components, and also put the importance of water into a wider human context its significant role in human history, its key role today, and potential role in future in the light of climate change and increasing global population pressures. The book is thoroughly up-to-date, contains over 100 diagrams and photographs to explain and amplify the concepts described, and contains over 750 references for further study